Najczęstsze powikłania po zabiegach chirurgicznej ekstrakcji trzecich zębów trzonowych żuchwy w materiale Zakładu Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi = The most common complications after surgery surgical extraction of mandibular third molars in the material of the Department of Oral Surgery, Medical University of Lodz - Aleksandra Szczepkowska; Małgorzata Lipczyńska; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2016)
Szczepkowska Aleksandra, Lipczyńska Małgorzata, Osica Piotr, Janas-Naze Anna. Najczęstsze powikłania po zabiegach chirurgicznej ekstrakcji trzecich zębów trzonowych żuchwy w materiale Zakładu Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi = The most common complications after surgery surgical extraction of mandibular third molars in the material of the Department of Oral Surgery, Medical University of Lodz. Journal of Education, Health and Sport. 2016;6(5):412-423. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53181 http://ojs.ukw.edu.pl/index.php/johs/article/view/3528     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Najczęstsze powikłania po zabiegach chirurgicznej ekstrakcji trzecich zębów trzonowych żuchwy w materiale Zakładu Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi   The most common complications after surgery surgical extraction of mandibular third molars in the material of the Department of Oral Surgery, Medical University of Lodz   Aleksandra Szczepkowska1, Małgorzata Lipczyńska2, Piotr Osica1, Anna Janas-Naze1     1. Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze   2. Studenckie Koło Naukowe przy Zakładzie Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze     Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71     Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Słowa kluczowe: chirurgiczna ekstrakcja zębów.   Key words: surgical extraction of teeth.           Streszczenie Ekstrakcja trzeciego zęba trzonowego żuchwy stanowi jeden z najczestszych i zarazem najtrudniejszych zabiegów chirurgii stomatologicznej. Celem pracy była analiza występowania powikłań po zabiegu chirurgicznej ekstrakcji trzecich zębów trzonowych żuchwy w materiale Zakładu Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi. Materiał i metody: Badaniem retrospektywnym  objęto 792 pacjentów (476 kobiet i 316 mężczyzn) przyjętych w Zakładzie Chirurgii Stomatologicznej w latach 2012-2015 celem ekstrakcji zatrzymanych całkowicie lub częściowo trzecich zębów trzonowych żuchwy. Analizie poddano wystąpienie powikłań takich jak szczękościsk, długotrwały obrzęk, zapalenie zębodołu, parestezje nerwu zębodołowego dolnego i/lub językowego w zależności od płci pacjenta  i wieku. Zgromadzone dane poddano analizie statystycznej przy pomocy oprogramowania Statistica 12.0. Wyniki: W materiale Zakładu Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi znalazło się 792 pacjentów, u których wykonano w sumie 1032 ekstrakcje. Średnia wieku przebadanych pacjentów wynosiła 28,7 lat. W grupie kobiet średnia wieku wyniosła 26,77 , podczas gdy w grypie mężczyzn - 29,86. Najmłodszy pacjent miał 14 lat, zaś najstarszy operowany - 74 lata. Powikłania wystąpiły u 183 pacjentów, w tym 121 kobiet i 62 mężczyzn. Najczęściej występującym powikłaniem pozabiegowym był szczękościsk, po nim: parestezje nerwu zębodołowego dolnego i/lub językowego oraz zapalenie zębodołu. U 25 pacjentów wystąpiło równocześnie więcej niż jedno powikłanie. Wnioski: Nie można jednoznacznie przewidzieć, czy powikłania wystąpią i u jakiej grupy pacjentów, jednak czynnik ludzki, jakim jest doświadczenie operatora i jego przygotowanie merytoryczno-manualne do wykonania tak trudnego zabiegu, jakim jest ekstrakcja trzeciego trzonowca, może mieć tu bardzo istotne znaczenie.         Summary Extraction of mandibular third molar is one of the most common and also the most difficult procedures in dental surgery. The aim of the study was to analyze the occurrence of complications after surgical extraction of mandibular third molars in the material of the Department of Oral Surgery, Medical University of Lodz. Material and Methods: Retrospective study included 792 patients (476 women and 316 men) adopted at the Department of Dental Surgery in 2012-2015 aim of extracting retained totally or partially third mandibular molars. We analyzed the occurrence of complications such as lockjaw, prolonged swelling, alveolitis, inferior alveolar nerve paresthesia and / or language depending on the patient's gender and age. The collected data were statistically analyzed using the software Statistica 12.0. Results: In the material of the Department of Surgery, Medical University of Lodz, there were 792 patients who underwent a total of 1,032 extractions. The average age of patients studied was 28.7 years. In women, the average age was 26.77, while in the men flu - 29.86. The youngest patient was 14 years old, while the oldest operated - 74 years. Complications occurred in 183 patients, including 121 women and 62 men. The most common postoperative complication was lockjaw, followed by: inferior alveolar nerve paresthesia and / or language, and alveolitis. In 25 patients experienced at the same time more than one complication. Conclusion: It can not unequivocally predict if complications occur and in which a group of patients, but the human factor, which is the experience of the operator and the preparation of substantive and manual to perform such a difficult surgery, which is the extraction of third molar, can be very important here.